Peran Remaja Milenial Terhadap Transformasi Desa Wisata Religi Menuju Desa Wisata Halal Studi di Desa Rogoselo - Adinugraha, Hendri Hermawan; Happy, Firman; Ma'ruf, Hasan; Wahid, Maulida Isnanini Afwa (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to describe the role of millennial youth in the transformation of a religious tourism village to a halal tourism village in Rogoselo village. This research is a qualitative research with a phenomenological approach. The data collection technique used in this research is the triangulation method, namely participant observation, in-depth interviews, and documentation. The findings of this study explain the concept of millennial youth participation in the transformation of religious tourism to halal tourism in Rogoselo village. It has provided insight into how an organization in Rogoselo village (BUMDes, Pokdarwis, and Karang Taruna) can and should manage its potential human resources to advance the village through the agricultural tourism sector in rural areas. The participation and collaboration of youth and Rogoselo village communities has increased and contributed to the process of transforming religious tourism into halal tourism. These findings are called the millennial based halal tourism village, which is a collaborative participatory model for millennial youth and rural communities in realizing the transformation of religious tourism towards halal tourism in Rogoselo village which is more equitable and just.